EFEKTIVITAS ANTIVIRUS CIDOFOVIR PADA PASIEN CACAR MONYET DENGAN GEJALA BERAT - Signa Radityatama, I Gusti Lanang Agung; Suprapti, Herni (Calvaria Medical Journal, 2024)
Background: Monkey pox is an infectious disease caused by viruses of the family Poxviridae, genus Orthopoxvirus, which can infect humans, vertebrates and arthropods. Symptoms of monkey pox include increased body temperature, headache, muscle aches, weakness, swollen lymph nodes in the neck, armpits and groin, and skin rashes. Giving antivirals is very effective in treating monkey pox infections caused by the monkey pox virus. Cidofovir is an antiviral that is given intravenously, for the treatment of monkey pox patients. The effectiveness of cidofovir in cases of monkeypox in humans is still uncertain. However, this drug has been shown to fight poxviruses in in vitro and animal studies. Based on this background, researchers are interested in conducting research on "Effectiveness of the Antiviral Cidofovir in Monkeypox Patients with Severe Symptoms". Method: This research is descriptive qualitative research with library research. Search for articles in this literature review using the 2010-2022 database with keywords according to the topic. After getting the reference sources, they were filtered until they got 25 journals consisting of 15 international journals, 10 national journals, and 2 textbooks. Result: The results of a literature study in 11 research journals were found to show the effectiveness of the antiviral cidofovir in monkey pox patients with severe symptoms, with recovery between 14-21 days at the fastest and between 35-52 days at the longest. Conclusion: The antiviral cidofovir is effective for treating monkeypox with severe symptoms. Apart from that, it was also found that the cure rate for monkey pox patients treated with cidofovir reached 57% -85% depending on the severity of the disease.